ChemInform Abstract: Catalytic Aerobic Oxidation and Tandem Enantioselective Cycloaddition in Cascade Multicomponent Synthesis. Issue 32 (August 2015) - Potowski, Marco; Merten, Christian; Antonchick, Andrey P.; Waldmann, Herbert
Abstract Copper catalyzed aerobic oxidation of cyclopentadiene to cyclopentadienone and subsequent asymmetric 1, 3‐dipolar cycloaddition of azomethine ylides produces tricyclic ketones with excellent diastereo‐ and enantioselectivities.